Belarusian entrepreneurs: 30 years of evolution of behavioral strategies - Andras, Iryna A. (Journal of the Belarusian State University. Sociology, 2019)
The aim of the study is within T. Zaslavskaya’s theoretical model of societal transformation to determine the key development stages of small entrepreneurship in Belarus depending on the impact of politico-administrative activity and reformative activity of authorities on socio-innovative activity of entrepreneurs. Historico-sociological approach to the development of entrepreneurship in Belarus is based on the analysis of books, articles, official documents and state statistics. We found out that the reformative activity of the authorities towards entrepreneurship is absolutely dependent on politicoadministrative influence. That is why the behavioral strategies of entrepreneurs are formed as reaction-adaptive behavior. The results of the study are primarily applicable for post-Soviet republics and countries with transition economy.
Keywords: entrepreneurship; entrepreneur; authorities; politico-administrative activity; reformative activity; socioinnovative activity; behavioral strategies